(3fXe GdLhOI heJWdHGJ JShjb GdNOeGJ GdJYdjejIs - (3dejGA eMeO(B, (3CMeOs; (3SYjO ESeGYjd Ydj(B, s ((3GdbGgQI(B:s (3GdecJHI GdYUQjI ddfTQ hGdJhRjY(B,s, 2009)
(3jVe eUWdMGJ hOQGSGJ CSGSjI, KbGaI GdLhOI hGdeYGjjQ, JSGDdGJ Mhd GdLhOI hGdEYJeGO aj GdJYdje, eSJbHd fXe GdEYJeGO GdeDSSj ddLGeYGJ GdeUQjI OQGSI MGdI, Odjd GSJQGJjLj dJhSjY fWGb LhOI GdNOeGJ GdLGeYjIs
(3GdeQGLY U(B.299 (3GdedGMb U(B.315s
Keywords: (3GdJYdje GdLGeYjs; (3GdJYdje(B- (3VHW GdLhOIs; (3GdLGeYGJ hGdcdjGJ(B- (3Jbjjes